2013
DOI: 10.1007/s12272-013-0099-1
|View full text |Cite|
|
Sign up to set email alerts
|

Design, synthesis, in vitro cytotoxicity evaluation and structure–activity relationship of Goniothalamin analogs

Abstract: A series of six/five member (E/Z)-Goniothalamin analogs were synthesized from commercially available (3,4-dihydro-2H-pyran-2-yl)methanol/5-(hydroxymethyl)dihydrofuran-2(3H)-one in three steps with good to moderate overall yields and their cytotoxicity against lymphoblastic leukemic T cell line (Jurkat E6.1) have been evaluated. Among the synthesized analogs, (Z)-Goniothalamin appeared to be the most active in cytotoxicity (IC50 = 12 μM). Structure-activity relationship study indicates that introducing substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…25 Yield: 3.64 g, 84%; white solid, mp 298−300 °C; (3-Fluorobenzyl)triphenylphosphonium Bromide (2e). 27 Yield: 3.96 g, 88%; white solid, mp 312−314 °C; 1 H NMR (400 MHz, DMSO-d 6 ): δ 7.95−7.89 (m, 3H), 7.82−7.68 (m, 12H), 7.30 (dd, J = 14.5, 7.6 Hz, 1H), 7.22−7.05 (m, 1H), 6.88 (d, J = 7.5 Hz, 1H), 6.79 (d, J = 9.9 Hz, 1H), 5.34 (d, J = 15.9 Hz, 2H). 13 [1-(4-Bromophenyl)ethyl]triphenylphosphonium Bromide (2k).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…25 Yield: 3.64 g, 84%; white solid, mp 298−300 °C; (3-Fluorobenzyl)triphenylphosphonium Bromide (2e). 27 Yield: 3.96 g, 88%; white solid, mp 312−314 °C; 1 H NMR (400 MHz, DMSO-d 6 ): δ 7.95−7.89 (m, 3H), 7.82−7.68 (m, 12H), 7.30 (dd, J = 14.5, 7.6 Hz, 1H), 7.22−7.05 (m, 1H), 6.88 (d, J = 7.5 Hz, 1H), 6.79 (d, J = 9.9 Hz, 1H), 5.34 (d, J = 15.9 Hz, 2H). 13 [1-(4-Bromophenyl)ethyl]triphenylphosphonium Bromide (2k).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As a part of our interest (Mohideen et al, 2013;Rahman et al, 2009;Sono et al, 1994;Zimmer et al, 1999) on searching new biological active molecules, a series of 8-(substituted)-aryloxycaffeine (3a-m) were synthesized from 8-bromocaffeine (2). Initially, 8-bromocaffeine (2) was prepared using bromine and sodium acetate in acetic acid at 60°C from commercially available 1.…”
Section: Chemistrymentioning
confidence: 99%
“…The α,β‐unsaturated lactone acts as a Michael acceptor, and its absence results in the complete loss of cytotoxic activity against cancer cells, while the exo double bond provides the required rigidity for higher activity . Thus, the benzene ring remains the most evident site for structural modifications, and a great amount of effort has been made in this direction . Our research group previously found that ( R )‐, ( S )‐, and rac ‐goniothalamin show no statistically significant difference in their in vivo cytotoxic activities in an Ehrlich solid tumor model .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Thus, the benzene ring remains the most evident site for structuralm odifications, and ag reat amount of effort has been made in this direction. [14,[20][21][22][23] Our research group previously found that (R)-, (S)-, and rac-goniothalamin show no Twos eries of racemic goniothalamin analogues displaying nitrogen-containing groups were designed and synthesized. A total of 19 novel analogues were evaluated against ap anel of four different cancer cell lines, along with the normal prostate cell line PNT2 to determine their selectivity.A mong them, goniothalamin chloroacrylamide 13 e displayed the lowest IC 50 values for both MCF-7 (0.5 mm)a nd PC3 (0.3 mm)c ells, about 26-fold more potent than goniothalamin (1).…”
Section: Introductionmentioning
confidence: 99%